2012
DOI: 10.1007/s10457-011-9473-5
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected lack of influence of tree rows on the dynamics of wheat aphids and their natural enemies in a temperate agroforestry system

Abstract: Trees at low density and cereals may be combined in silvoarable agroforestry systems: tree rows and their companion vegetation introduce an heterogeneity in the cropped field that may modify the dynamics of insects crop pests and their predators. This hypothesis was tested in tree-wheat systems by monitoring aphids and their predators for two years in southern France, in two fields in 2006 and one in 2007. Tree row vegetation diversity was either suppressed by weeding or stimulated by seeding flowering species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…There is a substantial amount of AF research in Europe. Most studies deal with ecological aspects, such as carbon sequestration, nutrient competition, root length and root interaction of trees and crop (Quinkenstein et al, 2009;Plieninger, 2011;Smits et al, 2012;Upson and Burgess, 2013;Cardinael et al, 2015a,b;Medinski et al, 2015). A recent study of Torralba et al (2016) showed a beneficial effect of AF on biodiversity and ecosystem services.…”
Section: Introductionmentioning
confidence: 99%
“…There is a substantial amount of AF research in Europe. Most studies deal with ecological aspects, such as carbon sequestration, nutrient competition, root length and root interaction of trees and crop (Quinkenstein et al, 2009;Plieninger, 2011;Smits et al, 2012;Upson and Burgess, 2013;Cardinael et al, 2015a,b;Medinski et al, 2015). A recent study of Torralba et al (2016) showed a beneficial effect of AF on biodiversity and ecosystem services.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of three invertebrate taxa across three UK silvoarable systems, higher numbers of spiders and fewer slugs were captured in arable alleys adjacent to understoreys sown with a grass-clover mix than unvegetated understoreys, while the responses of carabid beetles varied according to species and site [25]. In a subsequent study in a silvoarable system in France, understoreys sown with a flower mix had no observable effect on grain aphid colonies or their natural enemies in the adjacent crop, although the flower mix did not establish as intended [26]. However, there remains a lack of evidence for the effects of these various understorey management options on both biodiversity and, of more relevance to farmers, financial outputs [27].…”
Section: Introductionmentioning
confidence: 99%
“…In a well-managed agroforestry system, growing crops like wheat under tree canopies (e.g. Eucalyptus) provides favorable microclimatic conditions for the crops [ 17 , 76 , 77 ]. Tree canopy structure and distance from crops affects crop performance [ 21 , 19 , 23 ].…”
Section: Discussionmentioning
confidence: 99%